2014
DOI: 10.1161/circresaha.114.303200
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Cardiotoxicity Increases Mortality After Myocardial Infarction

Abstract: Rationale Sorafenib is an effective treatment for renal cell carcinoma, but recent clinical reports have documented its cardiotoxicity through an unknown mechanism. Objective Determining the mechanism of sorafenib-mediated cardiotoxicity. Methods and Results Mice treated with sorafenib or vehicle for 3 weeks underwent induced myocardial infarction (MI) after 1 week of treatment. Sorafenib markedly decreased 2-week survival relative to vehicle-treated controls but echocardiography at 1 and 2 weeks post-MI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 65 publications
1
61
0
1
Order By: Relevance
“…Our laboratories have studied myocyte regeneration in multiple small and large animal cardiac injury models, including continuous ISO infusion via osmotic minipumps 5 , myocardial infarction 14 , myocardial infarction in the presence of cardiotoxic agents 15 , and myocardial infarction with exogenous implantation of CSCs 14 . All of these studies have shown low rates (< 1%) of new myocyte formation.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratories have studied myocyte regeneration in multiple small and large animal cardiac injury models, including continuous ISO infusion via osmotic minipumps 5 , myocardial infarction 14 , myocardial infarction in the presence of cardiotoxic agents 15 , and myocardial infarction with exogenous implantation of CSCs 14 . All of these studies have shown low rates (< 1%) of new myocyte formation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these cardiovascular toxicities, hypertension and bleeding are most frequent adverse events associated with sorafenib therapy (18). Although there have been reports of cardiotoxicity from the long-term sorafenib therapy of patients with renal cell cancer and lung cancer, the present case is the first report of cardiotoxicity caused by long-term sorafenib therapy in a patient with advanced HCC; this adverse effect has been underestimated by phase III studies due to the relatively short-term treatment (19,20). The present case encourages the clinician to monitor cardiac toxicity during sorafenib therapy, particularly in elderly patients with underlying cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, bevacizumab given after acute myelogenous leukemia chemotherapy resulted in an increase in cardiovascular toxicity, although the mechanisms for this toxicity remain unknown [73]. Sorafenib has also been demonstrated to cause cardiotoxicity in mice due to myocyte necrosis [74]. Table 2.…”
Section: Side Efects Of Anti-vegf Medicationsmentioning
confidence: 99%